The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1159/000079914
|View full text |Cite
|
Sign up to set email alerts
|

Portosystemic Shunt Prevents Apoptosis in Rat Intestinal Mucosa Caused by Total Hepatic Ischemia

Abstract: Background: Prolonged splanchnic congestion due to total hepatic ischemia (THI) has been shown to induce damage to the intestinal mucosa. The present study was conducted to examine whether the protective effect of portosystemic shunt (PSS) can be seen on apoptosis of intestinal mucosa in a rat model of THI. Methods:Adult male Wistar rats were divided into the following 3 groups: control group; the THI group underwent THI for 30 min, and the PSS group was subjected to THI for 30 min with PSS. Rats were killed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Liver transplantation requires the portal vein to be blocked, causing intestinal congestion, hypoxia in the anhepatic phase and the restoration of blood flow reperfusion, making intestinal ischemia-reperfusion injury inevitable (4,5). Oxidative damage induced by reactive oxygen species (ROS), including the superoxide anion (O 2 − ), hydrogen peroxide (H 2 O 2 ) and the hydroxyl radical ( • OH), play a crucial role in the pathogenesis of ischemia-reperfusion injury (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver transplantation requires the portal vein to be blocked, causing intestinal congestion, hypoxia in the anhepatic phase and the restoration of blood flow reperfusion, making intestinal ischemia-reperfusion injury inevitable (4,5). Oxidative damage induced by reactive oxygen species (ROS), including the superoxide anion (O 2 − ), hydrogen peroxide (H 2 O 2 ) and the hydroxyl radical ( • OH), play a crucial role in the pathogenesis of ischemia-reperfusion injury (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the existence of antioxidative enzymes, including superoxide dismutase (SOD) and catalase (CAT), and antioxidants, including glutathione (GSH), the redox balance is well maintained and the clearance of ROS is promoted (8–10). Several studies have shown that inflammatory mediators, including tumor necrosis factor-α (TNF-α) and interleukin-1 (IL-1), are involved in the intestinal injury that is induced by liver transplantation (4,5). However, the exact alternative pattern of the oxidant/antioxidant system in the process of intestinal injury following liver transplantation remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…The portosystemic shunt has been reported as a surgical strategy to prevent splanchnic congestion associated with hepatic IR processes [26,27]. The blood pooling in the splanchnic bed induces portal hypertension, multivisceral edema, and a significant decrease in mesenteric arterial blood flow, culminating in intestinal ischemia [28].…”
Section: Discussionmentioning
confidence: 99%
“…Failure of intestinal barrier function when congestion occurs results in increased permeability to and subsequent translocation of bacteria and toxins from the lumen [30,31]. Recently, Bedirli et al demonstrated that splanchnic congestion after portal triad occlusion increases apoptosis in intestine and the use of a portosystemic shunt results in a reduction in the percentage of fragmented DNA, preserves the microscopic appearance of intestinal mucosa, and improves survival rate [27]. These results suggest that portosystemic shunt on hepatic, intestinal, and lung injuries associated with liver IR injury would be useful in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A isquemia hepática isolada pode levar ao colapso cardiovascular, como foi recentemente descrito por Bedirli et al (2004). Esses autores mostraram que, apesar da descompressão do território esplâncnico com do uso da derivação porto-sistêmica, dez por cento dos animais morreram refletindo os efeitos deletérios da isquemia isolada do fígado na circulação sistêmica.…”
Section: Variáveis Hemodinâmicas Sistêmicasunclassified